Design of floating treatment wetland in PT Antam Tbk UBP Bauksit Kalimantan Barat - Jannah Nurul; Putra Mirza Shofarisqi Taqwa (E3S Web of Conferences)
The wastewater that comes from bauxite ore washing at PT ANTAM Tbk UBP Bauksit Kalimantan Barat is not treated optimally, because of that it needs another alternative treatment other than coagulant. This research aims to establish the design of floating treatment wetland, arrange the application and maintenance procedure of floating treatment wetland, and arrange the draft cost budget of floating treatment wetland. The result of this research is design of floating treatment wetland plan that has 24 m2 or 4 x 6 m dimension with 600 plants for 1 unit. The selected plant is eleocharis dulcis which is able to absorb iron (FE) that contained in wastewater. Based on calculation if FA (bouyant force) higher than W (weight), than the media will be floated. All the design criteria from hydraulic loading rate, hydraulic retention time, water depth and surface coverage are accordant. The procedure of application and maintenance includes preparation and application procedure as well as operational and maintenance procedure. The cost required for 124 floating treatment wetland units is IDR 1.162.996.000.